2022
DOI: 10.3390/met12101695
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and Microstructure Evolution of High-Strength Al-Zn-Mg-Cu Alloy

Abstract: An isothermal compression experiment was conducted to study the rheological behavior of Al-4.57Zn-1.50Mg-1.92Cu high-strength aluminum alloy at strain rates ranging from 0.1 to 20 s−1 and temperatures in the range of 573 to 773 K. Then, the effects of strain, strain rate, and deformation temperature on material deformation were investigated through orthogonal experiment analysis. According to the research results, strain rate and temperature had significant effects on the level of flow stress. Besides, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The deformation temperature was between 250 °C and 450 °C, and the deformation strain rate was between 0.01 s −1 and 10 s −1 ; the findings suggest that the stress levels decreased with higher temperatures or lower deformation strain rates. Cai et al [ 18 ] investigated the isothermal compression response of an Al-Zn-Mg-Cu alloy, and the experimental data indicated that the strength of the alloy decreased with increasing temperatures and retained a proportional relationship with the strain rate. The influence of thermal deformation conditions on mechanical performance was discussed, and the results were employed to optimize the hot processing of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation temperature was between 250 °C and 450 °C, and the deformation strain rate was between 0.01 s −1 and 10 s −1 ; the findings suggest that the stress levels decreased with higher temperatures or lower deformation strain rates. Cai et al [ 18 ] investigated the isothermal compression response of an Al-Zn-Mg-Cu alloy, and the experimental data indicated that the strength of the alloy decreased with increasing temperatures and retained a proportional relationship with the strain rate. The influence of thermal deformation conditions on mechanical performance was discussed, and the results were employed to optimize the hot processing of the alloy.…”
Section: Introductionmentioning
confidence: 99%